Factors affecting customer satisfaction towards Islamic banking in Klang / Nurulfatin Shahida Ekmal Hisham - Ekmal Hisham, Nurulfatin Shahida (2015)
The title of this research is “Factors Affecting Customer Satisfaction towards Islamic Banking in Klang”. The purpose of this research is to determine the relationship between variables. There are four independent variables involve in this research which are service quality factor, ambience factor, accessibility factor and high profit rate factor. The dependent variable is customers’ satisfaction. In order to achieve this research, the hypothesis was created to test whether there is relationship between independent variables and dependent variable. Data obtain by using questionnaire which is the primary data. There were 150 selected respondents that answered the questionnaire based on their bank preferred, age, races, job sector and monthly income. This research had been conducted at five selected full – pledged islamic bank in Klang, Selangor which are Bank Rakyat, Al Rajhi Bank, BIMB, Muamalat and Kuwait Finance Bank House. From each of the bank only 30 respondents had been selected. The result shows a good result where all the independent variable had significant relationship with the customers satisfaction.